IDENTIFIKASI MAKNA KOMODIFIKASI TARI PIRING MELALUI PERSPEKTIF KOMUNIKASI NONVERBAL - Maula Waytisi Kirana (PRASI, 2023)
It is unavoidable that Indonesia only has a few performing arts due to the country's heterogeneity and the different ethnic groups that contribute to its varied cultures. One of these is the Piring dance (tari piring), a traditional Minangkabau plate dance from West Sumatra where the performers vigorously twist plates in different forms and swift movements while holding one in each hand. However, throughout time, this ritual dance has undergone commodification, in which the components of the performance have evolved into things that have economic worth and can be “purchased” and “sold”. Thus, this study aspires to ascertain these aspects’ nonverbal communication connotations both before and after commodification. The research used here is qualitative, with a literature study approach and data investigation through the descriptive analysis method. Research revealed that there were modifications to the musical accompaniment, clothing color, and movement. In conclusion, these components shifted from being used only to express appreciation to God to serving commercial interests. Because it provides insights into the evolving aspects of the Piring dance before and after commodification, which can be forgotten due to globalization, this research will be highly helpful for preservation. Keywords: Commodification, Piring dance commodification, Piring dance nonverbal communication.    Abstrak Sebagai negara yang heterogen dengan beragam suku bangsa yang menghasilkan banyak budaya, tidak memungkinkan Indonesia hanya memiliki sedikit seni pertunjukan. Tari piring, salah satunya, adalah tarian tradisional Minangkabau dari Sumatra Barat yang masing-masing tangan penarinya memegang piring dan memutarnya dengan kuat dalam berbagai formasi dan gerakan cepat. Namun, seiring berjalannya waktu, tarian ritual ini mengalami komodifikasi yang unsur-unsur pertunjukannya berubah menjadi sesuatu yang bernilai ekonomi dan dapat “diperjualbelikan”. Dengan demikian, penelitian ini bertujuan untuk mengetahui makna komunikasi nonverbal unsur-unsur tersebut sebelum dan sesudah komodifikasi. Melalui pendekatan studi literatur dan metode analisis deskriptif sebagai acuan pengkajian data, penelitian ini merupakan penelitian kualitatif. Setelah dilakukan penelitian, ditemukan adanya perubahan pada gerak, warna pakaian, dan musik pengiring. Kesimpulannya, unsur-unsur tersebut berubah dari yang murni hanya untuk menunjukkan rasa syukur kepada Tuhan menjadi tujuan komersial. Penelitian ini cukup substansial sebagai pelestarian karena memberikan wawasan tentang perubahan unsur-unsur tari piring sebelum dan sesudah komodifikasi yang dapat terlupakan melalui globalisasi.